DETERMINATION OF EFFICIENCY OF THE USE OF LABOUR FORCE BY USING INDEX OF QUANTITY OF PERSONS WITHOUT CERTAIN RESIDENCE AMONG WORKABLE POPULATION OF COUNTRY - Перевозова, Ірина Володимирівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In the article is conducted the review of such problem questions as determination of essence, criteria and index of efficiency of the use of labour force at different levels production processes; separate aspects of employment, optimization of qualifying parameters of labour force at the market of labour taking into account errors on such index (separate social phenomenon), as a quantity of persons without a certain residence among the working population of country.